Rethinking Self-Responsibility: An Alternative Vision to the Neoliberal Concept of Freedom. (January 2019) - Pendenza, Massimo; Lamattina, Vanessa
In current societies, the freedom of the individual is at the center of mainstream public and political debate. For neoliberals, the individual is conceived as an unattached, self-responsible market player. However, this perspective has highly destructive consequences for societies. We contrast this conception of the individual with that of Durkheim, endorsing Durkheim's. Our thesis is that the neoliberal notion of the individual, freedom, society, and the State rejects any idea of responsibility—of one individual toward others, of the State toward individuals, and even of individuals toward themselves—emphasizing the absolute autonomy of the individual. For neoliberals, society is an environment in which a new kind of individual is formed, whose modus vivendi is focused on self-entrepreneurship and the obsessive acquisition of resources to achieve success in a competitive system. In contrast, Durkheim highlights the moral nature of society and the reciprocal obligations of individuals. For him, the individual is part of the State, not against it, and, consequently, he considers neither the individual nor the State as subordinate to economic freedom and the needs of the market. Thus, Durkheim emphasizes a social vision with regard to freedom, justice, solidarity, and the responsibility of the individual and the State based on his perception that human behavior operates within particular fields of action that are formed by various social engagements.